2020
DOI: 10.3389/fchem.2020.586445
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ni-Modified ZSM-5 Zeolites and Their Catalytic Performance in n-Octane Hydroconversion

Abstract: Ni-modified ZSM-5 zeolites with different nickel contents were successfully prepared by the in situ synthesis method and the impregnation method. The synthesized samples were characterized by XRD, SEM, N2 adsorption–desorption isothermals, and Py-FTIR. The characterization results show that both the textural properties and crystallization of Ni-modified ZSM-5 zeolites were preserved well, and their acidic properties can be modulated after nickel modification. The corresponding NiMo catalysts supported on Ni-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
7
10
0
Order By: Relevance
“…This demonstrates a high degree of congruence with the pore pattern depicted in Fig. 4(b),(c), which agrees with the study by Wei et al 54 The corresponding pore-size distribution diagrams for adsorption and desorption are shown in Fig. 4(b),(c).…”
Section: Textural Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…This demonstrates a high degree of congruence with the pore pattern depicted in Fig. 4(b),(c), which agrees with the study by Wei et al 54 The corresponding pore-size distribution diagrams for adsorption and desorption are shown in Fig. 4(b),(c).…”
Section: Textural Propertiessupporting
confidence: 91%
“…The isotherms showed a hysteresis branch, which corresponds to a Langmuir isotherm (type IV) based on the IUPAC categorization, and the adsorption and desorption branches practically intersected at relatively low pressure, showing that the macro-mesoporous structures were well conserved after metal incorporation by the impregnation technique. [52][53][54] The adsorbed volume increased continuously with relative pressure. The improved adsorption in the pressure range of 0.4P/P 0 has occurred from the adsorption of nitrogen within and intra-crystalline mesopores as a result of the aggregation of the nanocrystals.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…The catalytic effect close to that of the monometallic Ni and Co loadings indicated that Ni and Co had a stronger adsorption capacity for fatty acids, which decreased the utilization of Mo active sites due to the competitive effect, and this contrast has been reported in published work. 25 In contrast, Mo 0.02 Cu 0.01 /Z-0.2M showed superior catalytic activity over monometallic loading catalysts Mo 0.02 /Z-0.2M and Cu 0.01 /Z-0.2M with a high overall TEX yield of 50.19 wt %, including 10.30 wt % in toluene, 3.82 wt % in ethylbenzene, and 36.07 wt % in xylene. It can be seen that Mo and Cu showed a certain synergistic effect.…”
Section: = × ×mentioning
confidence: 88%
“…ZSM-5 zeolite is a novel type of molecular sieve that contains organic amine cations synthesized by Mobil in the late 1960s. Its exceptional catalytic performance was attributed to its unique pore structure, adjustable acidic sites, and hydrothermal stability, which made it a promising catalyst in the petrochemical industry with increasingly diverse applications. ,, Meanwhile, it exhibited excellent catalytic performance in the esterification process . Therefore, ZSM-5 molecular sieves were commonly utilized as either carrier materials or direct catalysts in catalysis studies.…”
Section: Introductionmentioning
confidence: 99%